2015
DOI: 10.1186/s12052-015-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

Influencing highly religious undergraduate perceptions of evolution: Mormons as a case study

Abstract: Background: Students frequently hold an incorrect view of evolution. There are several potential barriers that prevent religious students, specifically, from engaging evolutionary theory in the classroom. This study focuses on two hypothesized barriers on learning evolutionary theory in a highly religious model population, specifically members of The Church of Jesus Christ of Latter-day Saints (LDS or Mormon): (1) religious views stemming from incorrect or inadequate understanding of the Mormon church's neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…More recently, the internal structure of the MATE in terms of the number and identity of measurable constructs (i.e., named sets of items measuring the same concept) has been found to be unclear. Wagler and Wagler challenged the content and internal structure validity for the MATE, and studies report the MATE represents one (Rutledge and Warden 1999;Rissler et al 2014;Deniz et al 2008), two (Romine et al 2017), four (Manwaring et al 2015), six (untested: Rutledge and Sadler 2007), or an unidentifiable number of constructs (e.g. Wagler and Wagler 2013;Hermann 2012Hermann , 2016Rowe et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the internal structure of the MATE in terms of the number and identity of measurable constructs (i.e., named sets of items measuring the same concept) has been found to be unclear. Wagler and Wagler challenged the content and internal structure validity for the MATE, and studies report the MATE represents one (Rutledge and Warden 1999;Rissler et al 2014;Deniz et al 2008), two (Romine et al 2017), four (Manwaring et al 2015), six (untested: Rutledge and Sadler 2007), or an unidentifiable number of constructs (e.g. Wagler and Wagler 2013;Hermann 2012Hermann , 2016Rowe et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the measurement scale has varied between four-, six-, and seven-point Likert scales. Notable implementations that introduce validity and reliability evidence are largely limited to Turkish populations (Akyol et al 2010(Akyol et al , 2012aIrez and Özyeral Bakanay 2011;Tekkaya et al 2012;Yüce and Önel 2015) with two notable studies (Manwaring et al 2015 andRomine et al 2017) providing the strongest evidence of internal structure validity with populations similar to the original American undergraduate implementations. The dearth of evidence regarding validity for the MATE pales in comparison to its diversity of implementations-an undesirable state indeed for measurements standards.…”
Section: Secondary Uses Of Focal Instrumentsmentioning
confidence: 99%
“…The data showed that this item had the highest number of accurate responses in comparison with all other items, suggesting that students were capable of responding scientifically to potentially controversial evolution statements. In addition, in a recently published study using subjects from the same institution, researchers found that student acceptance of evolution, as measured by the Measure of Acceptance of the Theory of Evolution (MATE), was over 80%, and knowledge of evolution, as measured by the Knowledge of Evolution Exam (KEE), was nearly 80% (19). This is in contrast to a study of students at the University of Minnesota, who scored an average of 54.2% on the KEE, and a study of life science faculty at a large Midwestern university, who scored 74.3% on the KEE and 87.6% on the MATE (20, 23).…”
Section: Discussionmentioning
confidence: 99%
“…This might lead to an understanding of religious 86 experience as standing in opposition to scientific exploration, and sets up intensity of religious 87 belief (or "religiosity") as a more direct way to test the relationship between religion and 88 evolution acceptance. Many studies have done so, and have found that increased religiosity is 89 associated with decreased acceptance of evolution (Brown, 2015;Carter & Wiles, 2014;Glaze et 90 al., 2015;Heddy & Nadelson, 2013;Lombrozo et al, 2008;Manwaring et al, 2015;Moore, 91 Brooks, & Cotner, 2011;Nadelson & Hardy, 2015;Rissler, Duncan, & Caruso, 2014;Trani, 92 2004). Religiosity, however, is a complicated construct (P. C. Hill & Hood, 1999), referring to 93 both intrinsic religiosity (the degree to which religion influences personal understanding and 94 decision making) and extrinsic religiosity (the importance of religious worship and religious 95 communities for an individual).…”
Section: Introduction 26mentioning
confidence: 99%